Navigating Geopolitical Crossfire: Oil Shocks, Digital Agility, and Sharia Governance in the Iran-Israel-US Crisis - Budi Sukardi; Nurizal Ismail (Journal of Islamic Economics and Finance Studies, 2026)
Abstract The geopolitical crisis centered on the escalating conflict between Iran, Israel, and the United States up to the end of 2026 has radically altered the global macroeconomic risk landscape. This study aims to analyze the impact of the shrinking economic stability space due to geopolitical shocks on the resilience of Islamic banking, exploring how the integration of digital agility and Sharia governance mediates these shocks. Using an explanatory thematic analysis method, this study explicitly establishes the Oil Digital Sharia or ODS framework as its primary theoretical contribution. The findings confirm that Middle Eastern political risks and structural oil price volatility transform systemic banking risk into decreased liquidity and increased non performing financing ratios, driven by inflation spikes above three percent. Although Islamic banks possess a stronger capital cushion than conventional banks, their resilience remains vulnerable to capital flight known as displaced commercial risk. This study confirms that resilience is actively constructed through a dual safety belt consisting of digital service transformation via artificial intelligence and strict Sharia board supervision backed by accounting and finance qualifications. This study recommends the need for central banks to design macroprudential instruments sensitive to geopolitical crises and urges Islamic banks in the Southeast Asian region to strengthen cyber risk mitigation within the framework of Islamic law compliance.   Abstrak Krisis geopolitik yang berpusat pada eskalasi konflik antara Iran, Israel, dan Amerika Serikat hingga akhir tahun dua ribu dua puluh enam secara radikal telah mengubah peta risiko makroekonomi global. Penelitian ini bertujuan untuk menganalisis pengaruh menyempitnya ruang stabilitas ekonomi akibat guncangan geopolitik terhadap resiliensi perbankan syariah serta menelusuri bagaimana integrasi ketangkasan digital dan tata kelola syariah memediasi guncangan tersebut. Dengan menggunakan metode analisis tematik eksplanatori, studi ini secara eksplisit menetapkan kerangka kerja Oil Digital Sharia atau ODS sebagai kontribusi teoretis utamanya. Temuan penelitian mengonfirmasi bahwa risiko politik Timur Tengah dan volatilitas struktural harga minyak mentransformasikan risiko sistemik perbankan menjadi penurunan likuiditas dan peningkatan rasio pembiayaan bermasalah yang dipicu oleh lonjakan inflasi di atas tiga persen. Meskipun bank syariah terbukti memiliki modal yang lebih kuat dari bank konvensional, ketahanan mereka rentan terhadap pelarian modal atau displaced commercial risk. Studi ini menegaskan bahwa resiliensi dikonstruksi secara aktif melalui sabuk pengaman ganda berupa transformasi layanan digital berbasis kecerdasan buatan dan keketatan pengawasan dewan syariah yang didukung kualifikasi akuntansi dan keuangan. Studi ini merekomendasikan perlunya bank sentral merancang instrumen makroprudensial yang peka terhadap krisis geopolitik serta mendesak perbankan syariah di kawasan Asia Tenggara untuk memperkuat mitigasi risiko siber dalam kerangka kepatuhan hukum Islam.